Multi-Agent Approach for facing challenges in Ultra-Large Scale systems - Hamid Bagheri; Mohammad Ali Torkamani; Zhaleh Ghaffari (International Journal of Electrical and Computer Engineering (IJECE), 2014)
The primary characteristics of ULS systems are ultra-large size, number of lines of code (LOC); number of people employing the systems; amount of data stored, accessed, manipulated, and refined; number of connections and interdependencies among software components; number of hardware elements. These characteristics of ULS systems make it impossible to rely on our current knowledge and techniques of software development. We will face fundamental challenges in the design and evolution, orchestration and control, and monitoring and assessment of ULS systems. In this paper we try to make a combination between ULS systems and Multi Agent Systems and to use Multi Agent System strengths to help tackling some challenges found in ultra-large scale systems. Banking system is an instance of ULS systems. As a case study, in a real project we have designed Automated Teller Machine (ATM) combination with biometric sensors based on multi-agent architecture.DOI:http://dx.doi.org/10.11591/ijece.v4i2.4102